Assembly of a Phragmites-associated Chloropidae (Diptera) fauna in North America: the Palearctic genus Cryptonevra Lioy in the Nearctic, and the genus Lipara Meigen in Canada - Barrie, Christine L.; Wheeler, Terry A. (Zootaxa, 2015)
A diverse Diptera assemblage, dominated by the family Chloropidae, is associated with common reed (Phragmites australis (Cav.) Trin. ex Steudel, Poaceae) in the Palearctic region (Tewksbury et al. 2002). Although P. australis has long been present in North America, many of its associated Chloropidae have remained restricted to the Palearctic.